The European long–range tracer experiment, ETEX: a database for comparing model results and for harmonisation purposes. (4th August 2014) - Archer, G.; Girardi, F.; Graziani, G.; Klug, W.; Mosca, S.; Nodop, K.; Stingele, A.
This report presents the layout and a summary of preliminary results of the European tracer experiment (ETEX), which was devised to serve several purposes, one of which was to create a database for long–range modelling.